PENYELESAIAN PERKARA DALAM PELANGGARAN PASAL 312 UNDANGUNDANG NOMOR 22 TAHUN 2009 TENTANG LALU LINTAS DAN ANGKUTAN JALAN DI WILAYAH HUKUM KEPOLISIAN RESOR KOTA PEKANBARU - Franky Dontin Tobing; Erdianto Efendi; Widia Edorita (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2015)
Hit and run case in traffic is a criminal offense that can lead to anxiety and raisesconcerns that quite disturbing and cause harm to the victims and the people who do not knowor have been victims of hit and run that agency is not responsible. The handling of a criminaloffense must be treated seriously by the police in order to resolve this infringement case.Therefore, the authors are interested in conducting research under the title Against CriminalLiability Violation of Article 312 of Law Number 22 Year 2009 regarding Traffic and RoadTransportation Law Regional Police in the city of Pekanbaru. Then to find out the barriersand drawbacks encountered in the implementation of criminal liability for violation of Article312 of Law Number 22 of 2009 on Traffic and Road Transportation Law On TerritoryPekanbaru City Police. The last to know the efforts to overcome the obstacles andweaknesses of the implementation of criminal liability for violation of Article 312 of LawNumber 22 of 2009 on Traffic and Road Transportation Law On Territory Pekanbaru CityPolice.In writing this essay, the author uses empirical approach or sociological law research.Regional research sites in Pekanbaru City Police Law. Data sources supported by theprimary data source, secondary. While data collection techniques are interviews and reviewof data using deductive method is to analyze the problems of a general nature then drawn toa conclusion in particular based on existing theories.From the results of research and discussion the authors to conclude that the First, theimplementation of criminal liability for violation of Article 312 Law on Traffic and RoadTransport are accountable for the basic errors which are intentional, but did not rule outbecause of an omission; Second, barriers experienced in the implementation of criminalliability for violation of Article 312 of Law Traffic and Road Transport Police Jurisdiction InPekanbaru City area that is a factor, the evidence is not numbered Police, facilities andinadequate infrastructure, lack of personnel, calling witnesses constraints, high cost in theprocess of investigation and inquiry; Third, the efforts made to overcome the obstacles andweaknesses in the implementation of criminal liability for violation of Article 312 of LawTraffic and Road Transport Jurisdiction In Pekanbaru City Police are making efforts toalleviate the criminal sanctions peaceful perpetrators of hit and run, mengomptimalkannumber of personnel, conduct coordination with the SAMSAT Pekanbaru, make socializationand education to the community, make Emergeny Call, perform intensive treatment inaccident-prone areas, to give understanding to people who are witnesses to come to addressthe witness was.Keywords: Criminal Liability, Breach, Hit and Run